Tinjauan Yuridis Pembatalan Surat Kuasa Yang Dibuat Oleh Notaris Tanpa Di Hadiri Dan Disetujui Oleh Salah Satu Pihak (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Abstract. Based on the title mentioned in this research, the aim of this research is to determine the juridical assessment of a power of attorney that was canceled by a notary without the presence of one of the parties and with their consent. This research uses a certain type of normative legal research. Library research was used in the process of collecting data from the items examined in this research. To evaluate and discuss research materials based on law, legal norms, legal theory and legal doctrine that are relevant to the main topic, this research uses a normative analysis approach to obtain the data. The results of this research indicate that the legal consequences of revoking a power of attorney carried out unilaterally by the director of PT Oro Jayanto Perkasa can be declared as an unlawful act. The director's legal responsibility for the revocation of the power of attorney made and signed before a notary is that the defendant is required to pay compensation to the plaintiff. So the government and the DPR should have the ability to test the power of attorney regulations in the Civil Code. and there should be outreach to the community to provide a clear understanding of the requirements that must be met in the handover of power